2018
DOI: 10.1177/1046496418797431
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Work Team Design Characteristics Across Industries: Combining Meta-Analysis and Comprehensive Synthesis

Abstract: This article presents a comprehensive synthesis and quantitative review of studies examining relationships between team design characteristics and team performance. Across 398 primary studies, the present study meta-analytically investigated the effects of team composition, team task design, and team leadership characteristics on team performance. The study further investigates how the effects of these team design characteristics differ according to the industry context within which the team is embedded (high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(88 citation statements)
references
References 171 publications
(251 reference statements)
5
74
2
2
Order By: Relevance
“…In order to measure team tenure, participants responded to the following prompt: “How long have you been working in this team?” Team average tenure was calculated by taking the average response of member's tenure on each team. This type of aggregation method for team tenure is in line with previous research (Carter et al, 2019).…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…In order to measure team tenure, participants responded to the following prompt: “How long have you been working in this team?” Team average tenure was calculated by taking the average response of member's tenure on each team. This type of aggregation method for team tenure is in line with previous research (Carter et al, 2019).…”
Section: Methodssupporting
confidence: 85%
“…Now we turn to team tenure, or the amount of time teams have spent working together. Prior research suggests that team tenure has important implications for team performance (Carter, Mead, Stewart, Nielsen, & Solimeo, 2019; Smith et al., 1994). We posit that gender‐diverse teams led by a leader high in vision communication should benefit more from the gender‐diverse composition of their team when they have more time working together; this will occur because teams will better recognize one another's expertise and will thus have enhanced information elaboration.…”
Section: Gender Diversity and The Cemmentioning
confidence: 99%
“…Empirically, too, evidence concerning the link between team virtuality and team performance is not so positive. Indeed, meta-analytic research has reported only very modest (i.e., close to zero) relationships between team virtuality and team performance (Carter, Mead, Stewart, Nielsen, & Solimeo, 2018), with a large heterogeneity in the observed associations between team virtuality and team performance across industries (Carter et al, 2018), research designs (Ortiz de Guinea, Webster, & Staples, 2012), and team types (e.g., student vs. organizational samples, short-term vs. long-term teams; Gibbs, Sivunen, & Boyraz, 2017). Altogether, research in this area has shown that team virtuality has positive, negative, and sometimes no effect on team performance (e.g., Gilson et al, 2015; Webster & Sandy Staples, 2006); these mixed results suggest that various factors potentially moderate (i.e., increase, decrease, or even reverse) the relationship between team virtuality and performance.…”
mentioning
confidence: 99%
“…Teamautonomie. Die Teamautonomie beschreibt das Ausmaß, in dem ein Team als Ganzes die Freiheit hat, seine Aufgaben und Vorgehensweisen zu bestimmen (Carter et al 2018). Sie kann anhand der Koordinationsstruktur beurteilt werden (Kim et al 2002): Für eine niedrige Autonomie steht eine sequenzielle Koordinationsstruktur, die sich auf ein schrittweises Vorgehen bezieht, das keine Abweichung von einer system-definierten, linearen Interaktionsprozedur zulässt.…”
Section: Arbeitsbezogene Ressourcenunclassified
“…Feedback bezieht sich auf Informationen, die dem Team zur Leistungssteigerung dienen sollen, und können von der Aufgabe oder von Personen (z. B. Teamleiterinnen und -leitern) stammen (Carter et al 2018;Geister et al 2006). Unterschieden werden kann zwischen Ergebnisfeedback, das Informationen zur Aufgabenperformanz beinhaltet, und Prozessfeedback, das sich auf den Prozess der Aufgabenumsetzung bezieht (Earley et al 1990).…”
Section: Arbeitsbezogene Ressourcenunclassified